If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 4n = 9 + 3n Solving 1 + 4n = 9 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 1 + 4n + -3n = 9 + 3n + -3n Combine like terms: 4n + -3n = 1n 1 + 1n = 9 + 3n + -3n Combine like terms: 3n + -3n = 0 1 + 1n = 9 + 0 1 + 1n = 9 Add '-1' to each side of the equation. 1 + -1 + 1n = 9 + -1 Combine like terms: 1 + -1 = 0 0 + 1n = 9 + -1 1n = 9 + -1 Combine like terms: 9 + -1 = 8 1n = 8 Divide each side by '1'. n = 8 Simplifying n = 8
| y=-5-0+2 | | -9x-21=6 | | 14.2-25.2=3.8+26.8 | | 6a-10=84+52 | | (1/8)x-6=-4 | | 3.4=8.8-0.9x | | -2x+13=3(x-7) | | 21+7u= | | 7x+92+6x+12=180 | | 4(m-1)-2m=16 | | 2x^2=-13x-20 | | 4t*3=5 | | X*.30=2.50 | | 5y-7=3y+21 | | 5x-4-2x=17 | | 2m/y=4 | | 5ln(X)=2.5 | | 1/12=3/8=5/12=5/8 | | 5=2x+16 | | 3/2m=8 | | y=-5-1+2 | | 9x^2(x+1)+6x(5+x)= | | 49-3x=4x | | -4n-2n=-16-4n | | 4w-2=26 | | 15-24/3 | | (7x/9)-12=x | | 6x-15=9-2x | | (-84=112)/2 | | 7x-9+4x+29=90 | | 6x+3x-7=38 | | (x/3)-7=0 |